Obstacles and Policy Measures Toward COVID-19 Vaccination: Creating a Sustainable Road Map for Malawi - Oladapo Rasaq Kayode; Onyinyechi Patience Obidiro; Usen Stephanie Lawrence; Afeez Babatunde Oyetola; Mohammad Mehedi Hasan; Adekunle Olajide; Olajide Mariam Olaitan; Zarmina Islam; Abdulhafeez Ayodele Mustapha; Eze Osuagwu-Nwogu; Shamas Ghazanfar; Olaleye Modinat Aderonke (Elsevier, 2022)
The Coronavirus Disease 2019 (COVID-19) pandemic is a public health threat for Malawi which is facing several challenges concurrently including disease burden; inadequate finances; illiteracy; and public mistrust in government. In this pandemic, vaccines are the most reliable and cost-effective public health intervention, and the Malawian government has instituted an action plan which includes prioritizing the vaccination of traditional and religious leaders, increased vaccination sites to include workplaces and shopping malls, and health promotion. However, there is still considerable hesitancy around the use of the available vaccines in Malawi. In this paper, we explore the multiple interrelated factors driving COVID-19 vaccine hesitancy in Malawi. It is therefore recommended that the Malawian government embrace multicomponent and wide-ranging strategies to address COVID-19 vaccine hesitancy in the country. This includes reviving trust in national health authorities by offering population-specific, target-driven, and effective, transparent, and timely communication to its citizens and relevant stakeholders about the safety and efficacy of the COVID-19 vaccine.